Peran Ranting Aisyiyah dalam Internalisasi Nilai-Nilai Kemuhammadiyahan di Karangasem Laweyan Surakarta Tahun 2015 - Latifah, Umi; , Dr. Mutohharun Jinan, M.Ag (2016)
Aisyiyah twig leadership of Karangasem is a part of Aisyiyah branch leadership of Laweyan, Surakarta. This organization were born because there is a deep concern to the condition of women who are bussy with domestic work, while KH. Ahmad Dahlan, the founder of Muhammadiyah assumed that women should be able to work in facing the society. Based on the background, this research aims to understand the role of Aisyiyah twig in leadership internalization of Kemuhammadiyahan values in Karangasem and to know what are the factors enabling and constraining so that the organization continues to run well. This research is a field research with qualitative descriptive approach. The research data are obtained by interview, documentation and observation and then the data are analized by descriptive analytic method. Based on data analysis, can be concluded that Aisyiyah twig in Karangasem plays role well in improving the knowledge of religion in society by organizing regular lectures every day 11 each month. More over they also establish a formal education to create an intelligent and religious generation. Supporting factors of this organization are a strong commitment of the board and also the support from the society who play an active role on the course of the existing activities. Then to be the hampering factors are difficulty of finding a new cadre to continue the organization as well as the lack of funds that they have.